2015
DOI: 10.1016/j.aqpro.2015.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of Phosphorus and Nitrogen with Canna x generalis Reeds in Domestic Wastewater through NMAMIT Constructed Wetland

Abstract: A proven method of removing contaminants from secondary wastewater being more recently embraced is bioremediation. This paper focuses on phytoremediation of excessive phosphorus and nitrogen using Canna x generalis reeds through a constructed wetland in the domestic wastewater of NMAM Institute of Technology (NMAMIT), Nitte, Udupi District, India. The 30.0m x 6.0m x 1.0m wetland was constructed as an adjoining facility to the Wastewater Treatment Plant (WTP) of the Institute, for postsecondary treatment. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…Usually, the incorporation in biological systems prevents the removal of phosphorous by the addition of flocculants and also by the operation of solid separation [51]. The results found for phosphorus removal showed how Hymenachne grumosa is effective for phosphorus removal as it was observed by [52].…”
Section: Resultsmentioning
confidence: 91%
“…Usually, the incorporation in biological systems prevents the removal of phosphorous by the addition of flocculants and also by the operation of solid separation [51]. The results found for phosphorus removal showed how Hymenachne grumosa is effective for phosphorus removal as it was observed by [52].…”
Section: Resultsmentioning
confidence: 91%
“…However, most researches still focus on the determination method in the food and environment (Bernardiet al, 2016, Da et al, 2018, Qin et al, 2016. Phytoremediation also was used as the removal of pesticide from the soils (Eevers et al,2017), for wetland vegetations, most researches were focused on the nitrogen and phosphorus removal from hydroponic media (Eevers et al, 2017, Hongxia et al, 2017, as a kind of wetland plant, canna was used as some organic pollutants and heavy mental's removal (Liu et al, 2015, Ojoawo et al, 2015, Subhashini and Swamy, 2014.This study confirmed that Canna was tolerant to 0.5 mg.l-1prometryn, which was a potential wetland plant for pollution remediation induced by herbicide.…”
Section: O N L I N E C O P Ymentioning
confidence: 99%
“…Canna plants not only remove pollutants from the environment and store them in their roots and rhizome, bull also transform some of the pollutants into nortoxic forms (Choudhary, 2011;Macci et al, 2015;Dong et al, 2016;Boonsaner et al, 2011;Cule N, 2012). This plant has experimentally been removed to produce a large amount of biomass in the eutrophic water system, develops a very thick strong fibrous root system in hydropic media, it can be used as phytormemediation plants for improving the water quality of aquaculture (Ojoawo et al, 2015;Chyan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Phytoremediation itself utilizes the ability of plants to absorb and eliminate water contamination. In the process, the plant is used as a waste treatment agent, to reduce, transfer, and stabilize contaminants in water [1]. This technique can be done by anyone and anywhere because it is quite easy and economical compared to other techniques [2].…”
Section: Introductionmentioning
confidence: 99%